The Results of Corneal Hydrops Treatment in Patients with Down Syndrome - K. Kh. Titoyan (Oftalʹmologiâ, 2018)
The article describes the clinical cases of acute keratoconus in three patients with Down syndrome who underwent penetrating  keratoplasty. Acute keratoconus were diagnosed in patients by examination of medical history, biomicroscopy, corneal topography,optical coherence tomography. Acute keratoconus occurs suddenly due to the rupture of Descemet’s membrane in the zone of itsstretching, when chamber moisture seeps into the thickness of the stroma, causing its swelling and perforation. If untreated, theprocess continues for 3–5 months. Most researchers recommend keratoplasty during the cold period of the disease. However, withthe threat of perforation require urgent surgical intervention. There are two effective methods of surgical treatment: epikeratophakiaand penetrating keratoplasty. Patients underwent penetrating keratoplasty. The preference for this method was given in connectionwith the following factors: young age patients (under 40 years), relatively healthy transparent peripheral zone of the cornea, whichwas observed in our patients, genetically determined diseases — Down syndrome, the threat of corneal perforation in the centre, apenchant for rubbing his eye, low vision other eye and the desire to obtain speedy optical effect along with the treatment. All patientsafter penetrating keratoplasty had improvement of visual acuity with observation periods up to 1 year. Due to the relatively highincidence of keratoconus in patients with Down syndrome should focus the attention of ophthalmologists. Thus, difficulties in thediagnosis of ophthalmic pathology in patients with concomitant Down syndrome can cause errors in verification of diagnosis and hencewrong treatment selection. In case of hydrops of the cornea penetrating keratoplasty is the choice treatment and contributes to the preservation of the eye and visual functions.